The Influence of Visual Merchandising and Store Layout on Company Performance in Matahari Department - I Gede Surya Nugraha; Ni Ketut Purnawati (Journal of Finance and Business Digital, 2023)
The entry of digitalization into the business world (e-commerce) in the past decade has become a serious challenge for retail store owners (offline stores) in Indonesia. Because, e-commerce provides efficient time and convenience in choosing the goods needed, which in turn makes people start leaving retail stores in fulfilling their life needs. However, not a few consumers are dissatisfied with e-commerce services between the expected products and those received. This study aims to determine the effect of visual merchandising and store layout on the performance of Matahari Department Store. The analytical method used is multiple linear regression with the t test. The results showed that store layout had a significant positive effect on company performance and visual merchandising had a significant positive effect on company performance.